The Avoidance Approach to Plural Value. Issue 160 (1st September 2019) - Brunning, Luke
Abstract : Value monists and value pluralists disagree deeply. Pluralists want to explain why moral life feels frustrating; monists want clear action guidance. If pluralism is true, our actions may be unable to honour irredeemably clashing values. This possibility could prompt pessimism, but the 'avoidance approach' to pluralism holds that although values may conflict inherently, we can take pre-emptive action to avoid situations where they would conflict in practice, rather like a child pirouetting to avoid the cracks on a pavement. Sadly, this view is hostage to epistemic problems and unforeseen consequences and is liable to generate timidity. It rests on the intuition that honouring values in action is more important than doing so in other ways, but this is a premise we have reason to reconsider.